2013
DOI: 10.1590/0004-282x20130086
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy is a safe and effective procedure for the treatment of Blake's pouch cyst

Abstract: OBJECTIVE: Blake's pouch cyst (BPC) is a midline cystic malformation of the posterior fossa, within Dandy-Walker's complex (DWC), often associated with hydrocephalus. Endoscopic third ventriculostomy (ETV) has been an alternative to conventional methods for BPC treatment. This study aimed at reporting our experience with ETV in a series of patients with BPC. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The procedure was ceased when the CSF has a clear appearance without any active bleeding. Report by Brusius and Cavalheiro showed usage of warmed normal saline was safe for irrigation in neonates and also has haemostatic effect if hemorrhage were to occur during the procedure [10]. There are two suggestions for the optimal timing for neuroendoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was ceased when the CSF has a clear appearance without any active bleeding. Report by Brusius and Cavalheiro showed usage of warmed normal saline was safe for irrigation in neonates and also has haemostatic effect if hemorrhage were to occur during the procedure [10]. There are two suggestions for the optimal timing for neuroendoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…23,26,27 At present, the scope of patients who can be successfully treated with endoscopic techniques is increasing. 3,9,12,14 In light of this, we present our experience using the combination of ETV and CPC (ETV+CPC) in the treatment of children with hydrocephalus of varied etiologies. It has been suggested that combining these techniques may lead to better results in treating these children, who form a major part of our clinical practice.…”
mentioning
confidence: 99%
“…They discussed that the patient’s hydrocephalus was caused by the combination of obstructed CSF flow at the fourth ventricular outlets and disequilibrium of the CSF dynamics between production and absorption capacity. Brusius et al 10) also reported that ETV was a safe and effective procedure for BPC-associated hydrocephalus. They demonstrated eight pediatric patients with BPC-associated hydrocephalus who were treated successfully by ETV.…”
Section: Discussionmentioning
confidence: 95%
“…2,[4][5][6][7][8][9] ETV has been reported to be effective in pediatric patients with BPCassociated hydrocephalus in recent years. 4,6,10) In line with the current trend of using minimally invasive procedures in neurosurgery, ETV is considered a good alternative for hydrocephalus with BPC.…”
Section: Introductionmentioning
confidence: 99%